Parents’ Roles in Using Technological Devices at the Elementary School - Anindita Fachrunnisa (EDUTECH, 2022)
The purpose of the study is to find out how the role of parents in the use of information and communication technology in online learning situations is carried out by their children who are at the elementary level. Due to the current pandemic conditions, elementary school students are learning at home online. With the assistance of parents, elementary school students must still be given directions in online learning using electronic communication tools. This study adopts a qualitative methodology with five participants who will be given a questionnaire by the researcher. The answers to each of these will then be analyzed as a result of this study. The results of this study reveal that the role of parents is very important in guiding, assisting, and supervising children in the use of electronic communication tools.